Improvement in the EFL Learning Process in VET Studies. A Structural Equations Model of Affective Variables: English Language Anxiety, Willingness to Communicate and Self-efficacy in English - Chaves-Yuste, Beatriz; de-la-Peña, Cristina; Pérez-Agustín, Mercedes (LEARN Journal: Language Education and Acquisition Research Network, 2024)
Vocational Education and Training (VET) is undergoing an international and national improvement process in order to achieve internationalization, among others. To this end, it is necessary to optimize the EFL level of VET students. Structural equation modeling (SEM) is used to analyze the direct and indirect effects of English language anxiety, willingness to communicate in English, and self-efficacy in English on the academic performance in EFL among VET students. The sample consisted of 100 Spanish VET students (75% female - 25% male) aged between 18 and 40 years old. Questionnaires on English language anxiety (FLCAS), willingness to communicate in English (WTC), and self-efficacy in English skills (listening, speaking, reading, and writing) were administered. In addition, academic grade was used to measure the performance in English. The proposed model received a satisfactory fit. The results show that English language anxiety significantly influences academic performance and has a medium effect on willingness to communicate in English. Practical implications for organizing English classes to improve English proficiency in VET are discussed.
Keywords: anxiety; willingness to communicate; self-efficacy; academic performance; EFL